Exploring newcomer women's embodied selves: culturally responsible qualitative research. Issue 4 (2nd October 2019) - Green, Amy R.; Kassan, Anusha; Russell-Mayhew, Shelly; Goopy, Suzanne
ABSTRACT: In recent years, several scholars have called for the construct of embodiment as a meaningful way to explore the ways in which women experience their bodies. However, limited research has explored embodiment specifically amongst newcomer women who are part of visible minority groups in Canada. Although embodiment theories acknowledge the central role of culture in shaping the ways individuals experience their bodies, it remains unclear if and how research can tap into newcomer women's embodiment in a way that is culturally responsible. Thus, this article will explore how the construct of embodiment offers a meaningful vantage point from which to conduct qualitative research with newcomer women, offering suggestions for working through some of the ethical, methodological, and cultural considerations that may arise in doing so. More specifically, strategies and considerations will be discussed for developing meaningful research questions, engaging in responsible recruitment, building research relationships, attending to culturally responsible data collection, and partaking in embodied reflexivity. Implications for counselling practice and social justice will also be provided.